Prioritas Pengembangan Infrastruktur Wisata di Pantai Corong, Kabupaten Penajam Paser Utara Berdasarkan Persepsi Pengunjung - Putri Fatimatuzzahroh Ilhami; Khairunnisa Adhar; Elin Diyah Syafitri; Srirahadita Pamungkas; Maryo Inri Pratama; Sarah Membala (Perencanaan Wilayah dan Kota, Institut Teknologi Kalimantan, 2025)
Pantai Corong has potential for further development; however, it still faces challenges related to inadequateinfrastructure. This study aims to identify tourism infrastructure development priorities based on visitorperceptions. The research employed a kuantitatif method approach with a rationalistic perspective, and data werecollected through questionnaires using the snowball sampling technique. The analysis was conducted using theLikert scale and Importance-Performance Analysis (IPA). The findings show that toilets and waste managementsystems are the most urgent facilities to be developed, as they are highly important but currently underperforming.Meanwhile, facilities such as food stalls, parking areas, and clean water networks are considered important andperform well, thus should be maintained. Other facilities, including accommodations and public transportation, areperceived as less important and are not the main focus for development at this time.